The Properties of Diesel Blends with Tire Pyrolysis Oil and Their Wear-Related Parameters - Leszek Chybowski; Marcin Szczepanek; Tomasz Pusty; Piotr Brożek; Robert Pełech; Andrzej Wieczorek (Energies)
This research presents the impact of diesel blends with tire pyrolysis oil (TPO) as an additive for minimizing the wear and tear of engine components. This study investigates the blends of normative diesel oil with TPO content ranging from 5% m/m to 20% m/m. Reference measurements are made for pure diesel oil (D100) and pure TPO. This investigation included an evaluation of the corrosion effect and the effect of the fuels tested on abrasive wear. For each fuel, the sulfur content, water content, lubricity (which is defined as the corrected average diameter of the wear trace during the high-frequency reciprocating rig (HFRR) test), and impurity content are determined. Impurities are assessed using indicators such as ash residue, coking residue from 10% distillation residue, determination of wear metals and contaminants, insoluble impurity content, and total sediment by hot filtration. All parameters are determined using recognized methods described in international standards. Approximation models are built for all the analyzed parameters, which can be used in future studies. At the same time, the individual values of the analyzed factors are compared with the threshold values specified in selected standards and regulations. Consequently, it is possible to assess the usefulness of individual fuels in terms of meeting the requirements for minimum wear of engine components. The results show the suitability of pyrolysis oil and the potential for its use as an additive to fossil fuels in terms of meeting most factors. Some of the fuels tested did not meet the standards for acceptable sulfur content. However, in terms of sulfur content, all of the analyzed fuels can be used to power watercraft and land-based power and thermal power plants equipped with flue gas desulphurization systems. A second indicator for not meeting the standards is the ash residue value, which indicates the high content of non-combustible, mainly metallic, substances in the pyrolysis oil used for the tests. Post-recycled oils must, therefore, undergo appropriate purification before being used as an additive to diesel fuels for internal combustion engines. Once the post-recycling oil has been subjected to desulfurization and advanced filtration, it can be used as a fuel additive for land vehicles, which fits in with closed-loop economies and sustainable development strategies.